Enhancing Early Childhood Education Teachers' Creativity through Professional Development Training Program - Kurniawati, Atit; Nurhayati, Sri; Rukanda, Nandang (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2024)
This study aimed to examine the implementation and impact of professional development on the creativity of early childhood educators, focusing on creating an innovative teaching medium known as the Magic Box. This research used a qualitative approach with a case study method; the research subjects comprised ten early childhood educators, one resource person, and one training manager. Data were collected using in-depth interviews, observations, and document studies. The Miles and Huberman method was used to analyze the collected data. The research findings reveal a substantial transformation in educators' creativity levels after participating in Magic Box's professional development and training programs. Through a structured and hands-on approach, educators gain practical experience and motivation to infuse creativity into their teaching practices. Educators report increased confidence in generating creative ideas for teaching materials and a shift in their instructional approach to encourage more engaging and interactive learning experiences for children.